The possible effects of chili peppers on ADHD in relation to the gut microbiota - Li, Yinyue; Feng, Jing; Ding, GuangYao; Deng, Lin; He, Ying; Zhang, Qiongqiong; Wang, Jianhui; Chen, Xia (Frontiers in Nutrition, 2025)
Attention deficit hyperactivity disorder (ADHD) is a common neurodevelopmental disorder, which is characterized by inattention, impulsivity and hyperactivity. Although the etiology and pathogenesis of ADHD are not fully understood, existing studies have shown that it may be related to genetic factors, environmental factors, abnormal brain development, and psychosocial factors. In recent years, with the concept of microbioa-gut-brain axis (MGBA), more and more studies have begun to pay attention to the effect of gut microbiota on ADHD. Dietary structure can significantly change the diversity and abundance of gut microbiota. Therefore, dietary supplements or food additives to regulate gut microbiota have become one of the potential ways to treat ADHD. Peppers, as an important dietary component, have potential value in regulating gut microbiota. Among them, capsaicin (8-methyl N-vanillyl-6-noneamide, CAP), as a key active component of peppers, has been shown to have potential therapeutic effects on central nervous system (CNS) diseases such as Parkinson’s disease, epilepsy, and depression. In addition, much attention has been paid to the beneficial effects of CAP on gut microbiota. Chili peppers contain not only CAP, but also rich in vitamin C and fatty acids, all of which may ameliorate ADHD by modulating the gut microbiota. This finding not only provides a potential treatment for ADHD, but also provides a new perspective to expand the research and clinical treatment of ADHD pathogenesis. Although current research on the potential therapeutic effects of chili peppers on ADHD is still at an early stage and requires further verification through larger-scale and more rigorous controlled studies, its potential clinical value cannot be ignored.